Antimicrobial Properties of Daucus nebrodensis Strobl.: A Multifunctional Essential Oil Against Bacterial Pathogens - Giusy Castagliuolo; Antonella Porrello; Maddalena Cerasola; Giuseppe Bazan; Dario Antonini; Mario Varcamonti; Maurizio Bruno; Anna Zanfardino; Natale Badalamenti (Plants)
Daucus is a large genus of the Apiaceae family, comprising around forty-five accepted species, that has a worldwide distribution. Species of this genus have been reported to have several traditional medicinal uses, and some of them are also largely used as food and spices. Daucus nebrodensis Strobl. is an endemic species of Sicily growing in the montane environments of the Madonie and the Nebrodi Mountains. In this work, the essential oil of D. nebrodensis (DnEO), collected wild near Messina (Italy), was chemically and biologically investigated. The hydrodistilled essential oil (yield 0.15%), obtained from fresh aerial parts, was evaluated by GC-MS, and It was particularly rich in monoterpene hydrocarbons, with sabinene (33.6%), α-pinene (17.2%), γ-terpinene (9.8%), and α-terpinene (7.6%) as the main metabolites. DnEO, and its main constituents, have been tested to evaluate their biological properties. Given the current problem of antibiotic resistance, it is of great interest to identify alternative molecules that could counteract the its progression. Therefore, DnEO was tested against Gram-negative species, such as E. coli DH5α and P. aeruginosa PAOI, and Gram-positive species, such as S. aureus ATCC6538P, B. subtilis AZ54, and M. smegmatis MC2155, showing notable antibacterial activity. The MIC for Bacillus subtilis, the most sensitive strain, was 18 mg/mL, while the MIC for Pseudomonas aeruginosa, the least sensitive strain, was 30 mg/mL. Moreover, interesting antibiofilm activity was observed against Mycobacterium smegmatis with a 55% inhibition. Its ability to form biofilms contributes to its persistence and resistance in clinical settings. These findings highlight the potential of D. nebrodensis EO as a source of bioactive compounds with promising antimicrobial and antibiofilm properties.